2020
DOI: 10.20944/preprints202007.0428.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Inclusions on the Corrosion Properties of Nickel Based Alloys 718 and EP718

Abstract: Inclusions in steels and alloys are known as factors that could lower deformation, mechanical, corrosion and other properties. Study of inclusions in nickel based alloys is important since these materials could suffer from corrosion degradation in harsh operational conditions, where inclusions could lead to a pitting initiation. For estimation of a harmful effect of different inclusions on corrosion resistance of Ni-based alloys, inclusion characteristics (such as composition, morphology, size, number and loca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It has been observed that in many liquid metal–solid systems, the formation of a new compound is preceded by the dissolution of the solid in the liquid [ 16 ]. The dissolution of a matrix near impurities or inclusions and clusters located in grain boundaries is more than 2 times larger than when compared to inclusions found inside the grains of the given alloy samples [ 57 ]. The initial dissolution rate is usually high, but once a layer of the new compound is formed at the interface, the dissolution rate decreases rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that in many liquid metal–solid systems, the formation of a new compound is preceded by the dissolution of the solid in the liquid [ 16 ]. The dissolution of a matrix near impurities or inclusions and clusters located in grain boundaries is more than 2 times larger than when compared to inclusions found inside the grains of the given alloy samples [ 57 ]. The initial dissolution rate is usually high, but once a layer of the new compound is formed at the interface, the dissolution rate decreases rapidly.…”
Section: Discussionmentioning
confidence: 99%